Synthesis of Curcumin Derivatives (2.5-Bis((E)-4-Hydroxy-3-Methoxy Benzylidine) Cyclopenta-1-On) from Vanillin and Its Activity Test Against Α-Glucosidase Enzymes - Rahma Diyan Martha; Danar Danar; Rini Retnosari (Walisongo Journal of Chemistry, 2022)
Synthesis of curcumin analogs (2.5-Bis((E)-4-Hydroxy-3-Methoxy Benzylidine) Cyclopenta-1-On) based on Claisen-Schmidt condensation using an acid catalyst and inhibition of glucosidase enzyme was carried out. The antidiabetic activity of curcumin analogs was carried out by the use of α-glucosidase enzyme from moldy rice (Oryza sativa). The curcumin analogs were synthesized by reacting the vanillin with cyclopentanone.  The structure of all products was confirmed by FTIR, GC-MS, 1H-13C-NMR spectrometers, and the activity enzyme. The results showed the curcumin analogs were yielded in 52.27%, respectively as yellowish-green solid. The inhibition test of the α-glucosidase enzyme showed that the curcumin analogs were the potential to inhibit the α-glucosidase enzyme with an inhibition percentage of about 94.26% in 5 mM.